Grammatical meaning and the second language classroom: Introduction. (March 2019) - Marsden, Heather; Slabakova, Roumyana
This special issue assembles empirical work on second language teaching and learning from a generative linguistic perspective. The focus is on properties that constitute grammar–meaning interaction that differ in the native and target language grammars, and that have not been highlighted in the pedagogical literature so far. Common topics address whether and how learners acquire grammatical meanings in the second language, including difficult misalignments between native and target-language constructions and functional morphemes. We propose that teaching and learning a second language can be enhanced by focusing on the relationship between grammatical forms and their meanings, as elucidated by contemporary linguistic theory.